Effects of dietary L-carnitine on growth performance, body composition and antioxidant status of beluga (Huso huso) and comparison with Bimar diet - Mohseni, M.; Pourkazemi, M.; Kazemi, R.; Taati, R. (2017)
A 17-week feeding trial was carried out to evaluate the effects of dietary L-carnitine level in beluga, Huso huso. A total of fish averaging 1247 ± 15.6 g (mean ± SD) were randomly distributed into 21 fibreglass tanks, and each tank holding 10 fish was then randomly assigned to one of three replicates of seven diets with 50, 150, 350, 650, 950 and 1250 mg L-carnitine kg-1 diet or control diet (Biomar). At the end of 17 weeks of feeding trial, average weight gain (WG), feed efficiency (FE), protein efficiency ratio (PER) and condition factor (CF) of fish fed 350 mg kg-1 diet were significantly (P < 0.05) higher than those of fish fed 50, 150, 950 and 1250 mg kg-1 diets. WG, FE, PER and CF of beluga fed 650 mg kg-1 diet or control diet (Biomar) were also significantly higher than those of fish fed 50, 950 and 1250 mg kg-1 diets. Whole body and muscle protein were significantly improved by the elevation of dietary L-carnitine level up to 350 mg kg-1. Liver superoxide dismutase and glutathione peroxidase activities of fish fed 350 and 650 mg kg-1 diets were significantly higher than those of fish fed other diets. The dietary L-carnitine level of 350mg kg-1 diet could improve growth performance, feed utilization, protein-sparing effects of lipid, immune response, antioxidant defence system and reproductive success. Published